The Weber's Law Implementation-The Fire and the Misfire - Justus, T. Frank Sunil; Sheikh Shadullah, S.; Najimudeen, K. (Indian Journal of Marketing, 2006)
The idea that people cannot always distinguish between two stimuli has marketing implications. The minimal difference that can be noticeable between two similar stimuli is known as the Differential Threshold or the Just Noticeable Difference (JND). Discovered by a 19th century German Scientist, E.H. Weber, the relationship between the size of the JND and intensity of the stimulus has come to be known as Weber's Law.